1981
DOI: 10.1128/jb.145.3.1325-1333.1981
|View full text |Cite
|
Sign up to set email alerts
|

Corresponding changes in kynurenine hydroxylase activity, membrane fluidity, and sterol composition in Saccharomyces cerevisiae mitochondria

Abstract: The effect of sterol composition on the properties of the mitochondrial membrane of Saccharomyces cerevisiae was investigated. The physical state of mitochondrial membranes from wild-type strains and sterol mutants was compared, using a fluorescence polarization technique with 1,6-diphenyl-1,3,5-hexatriene. Changes in the rate of depolarization of the probe molecule as a function of temperature suggest the occurrence of a phase transition in the mitochondrial membranes isolated from the sterol mutants but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 24 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…The strains of S. cerevisiae and their sterol phenotypes used in this study are summarized in Table 1. These strains and the defects in sterol biosynthesis have been characterized in previous communications (1,4).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The strains of S. cerevisiae and their sterol phenotypes used in this study are summarized in Table 1. These strains and the defects in sterol biosynthesis have been characterized in previous communications (1,4).…”
Section: Methodsmentioning
confidence: 99%
“…Sphaeroplasts were prepared by treatment with snail gut enzyme (1) or an extracellular lyticase from Oerskovia xanthineolytica (5). The lyticase was prepared by dialysis of the medium following growth of O. xanthineolytica on modified Sistrom's medium (5) against buffer containing 1.1 M sorbitol, 10 mM phosphate and 1 mM EDTA, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In organelles, such as mitochondria, in which membranes control the function of the organelle, it is essential to know how the sterol is distributed; Bottema and Parks (6) have found that the sterol-to-phospholipid molar ratio was very similar between the inner and outer membranes of yeast mitochondria. Additionally, the types of sterols present affect the physical properties of the mitochondrial membrane so that qualitative changes in the sterol components produce a wide range of fluidities (2,3,17,22).…”
mentioning
confidence: 99%